The analysis of sales promotion and content marketing influence on product purchase intentions in Tiktok Shop - Pratama Rizky Kautsar Lauw; Norhidayati Norhidayati (International Journal of Applied Finance and Business Studies, 2023)
This study aims to determine and analyze the influence factors of purchase intention through Tiktok Shop: sales promotion and content marketing are described partially and simultaneously. This research is based on a questionnaire survey, and the sampling technique used purposive sampling to 100 respondents. The data analysis technique employed multiple regressions analysis. The research is dedicated to help the sellers on TikTok Shop better understand marketing strategy, customer attitude, and behaviour while using Tiktok Shop. The results indicate that sales promotion and content marketing variables positively and significantly influence on purchase intentions of Tiktok Shop.